DETERMINANTS OF STUNTING INCIDENCE IN SUKARAME SUB-DISTRICT, TASIKMALAYA DISTRICT, JAWABARAT PROVINCE, INDONESIA - Purwanto, Anto; Nurjazuli, Nurjazuli; Setiani, Onny; Trijoko, Trijoko (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Stunting is a disorder of children's growth and development due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below standard. The prevalence of stunting in Indonesia continues to decline from 2018-2022. The incidence of stunting in toddlers is related to various factors such as sanitation and ETC Objective : The research aims to determine the distribution of stunting in the Sukarame District, Tasikmalaya Regency, West Java Province in 2024 Research Methods/ Implementation Methods : This study is an analytical descriptive research. The subjects targeted in this study are mothers who have stunted toddlers in February 2024, the inclusion criteria in this study are respondents who are declared stunted and willing to be interviewed. There were 341 stunting incidents in Sukarame District Results : Based on the results of the study, there are several determinants of stunting in Sukarame District, namely access to healthy latrines has only reached (77.7%), there are still (12.6%) people who do not have access to proper drinking water, there are (7%) mothers of stunted toddlers who experience KEK during pregnancy and only (30%) families of children under five who have BPJS/JKN Conclusion/Lesson Learned : Based on research that has been conducted in Sukarame Subdistrict, Tasikmalaya Regency, there are four main factors that influence the incidence of stunting in children under five years old, namely: 1. Community access to healthy latrines 2. Community access to proper drinking water 3. Chronic Energy Deficiency (CHD) in pregnant women 4. BPJS National Health Insurance coverage.